The nuclear pore protein Nup153 associates with chromatin and regulates cardiac gene expression in dystrophic mdx hearts. Issue 2 (13th August 2016) - Nanni, Simona; Re, Agnese; Ripoli, Cristian; Gowran, Aoife; Nigro, Patrizia; D'Amario, Domenico; Amodeo, Antonio; Crea, Filippo; Grassi, Claudio; Pontecorvi, Alfredo; Farsetti, Antonella; Colussi, Claudia
Abstract: Aims: Beyond the control of nuclear-cytoplasmic trafficking nucleoporins regulate gene expression and are involved in cardiac diseases. Notably, a number of cardiovascular disorders have been linked to alterations in epigenetic mechanisms. Here we aimed to determine the contribution of Nup153 to the epigenetic alterations occurring in cardiomyopathy of dystrophin-deficient mdx mice (C57BL/10ScSn-Dmd mdx /J). Methods and results: Nup153 was lysine-acetylated and its expression was significantly increased at protein level in mdx hearts compared with controls. Accordingly, lysine acetyl transferase (KAT) activity associated with Nup153 was higher in mdx hearts paralleling increased binding with the lysine acetylases P300/CBP-associated factor (PCAF) and p300. Interestingly, Nup153 silencing in mdx organotypic heart tissue slices caused a reduction in PCAF- and p300-specific activities. Remarkably, the level of nitric oxide (NO), which is reduced in mdx mice, was important for KAT-dependent regulation of Nup153. In fact, treatment of mdx heart tissue with an NO donor or the KAT inhibitor anacardic acid normalized Nup153 protein expression. Nup153 was recruited to chromatin and regulated the transcription of genes involved in cardiac remodelling, including the actin-binding protein nexilin. Accordingly, nexilin protein expression was abrogated by Nup153 silencing in mdx organotypic cultures. Electrophysiological and molecular experiments revealed that Nup153 overexpression in normal cardiomyocytes increases Ca v 1.2 calcium channel expression and function. Alterations in Nup153 protein expression and intracellular localization were also found in dystrophic cardiomyocytes derived from patient-specific induced pluripotent stem cells. Importantly, Nup153 up-regulation and increased acetylation were also found in the heart of Duchenne muscular dystrophy patients. Conclusions: Our data indicate that Nup153 is an epigenetic regulator which, upon altered NO signalling, mediates the activation of genes potentially associated with early dystrophic cardiac remodelling.